Proposal for a Tourism Competitiveness Model for Business Entrepreneurship in the Department of Boyacá Post-Covid 19 - Conde, Efrén Ariolfo Báez; Moreno, Olga Rocío Márquez; Molina, Roberto Carlos Vega (Journal of Posthumanism, 2025)
Background: The department of Boyacá, Colombia, faces market conditions on supply and demand, in the post-Covid-19 era that require the proposal of a tourism model applicable to both short and long-distance destinations. Method: This article proposes a tourism competitiveness model for the intricacy of the tourism sector, accentuating the transversality and interaction of all the actors involved. It considers the influence of the internal and external environment, backed up by the country risk factor, which can significantly impact tourists' decisions about destinations in Boyacá. Results: The model is structured in three phases: evaluation, qualification, and the decision that a potential tourist faces when selecting their destination. Conclusions: The model's application in this context provides insights into the impact of supply conditions and adequate preparation on the long-term competitiveness and sustainability of the regional tourism sector, and consequently, on local communities.